Increase in coleoptile length and establishment by Lcol-A1, a genetic locus with major effect in wheat - Bovill, William D.; Hyles, Jessica; Zwart, Alexander B.; Ford, Brett A.; Perera, Geetha; Phongkham, Tanya; Brooks, Brenton J.; Rebetzke, Gregory J.; Hayden, Matthew J.; Hunt, James R.; Spielmeyer, Wolfgang (BMC plant biology, 2019)
Good establishment is important for rapid leaf area development in wheat crops. Poor establishment results in fewer, later-emerging plants, reduced leaf area and tiller number. In addition, poorly established crops suffer from increased soil moisture loss through evaporation and greater competition from weeds while fewer spikes are produced which can reduce grain yield. By protecting the emerging first leaf, the coleoptile is critical for achieving good establishment, and its length and interaction with soil physical properties determine the ability of a cultivar to emerge from depth. Here we characterise a locus on chromosome 1AS, that increases coleoptile length in wheat, which we designate as Lcol-A1. We identified Lcol-A1 by bulked-segregant analysis and used a Halberd-derived population to fine map the gene to a 2 cM region, equivalent to 7 Mb on the IWGSC genome reference sequence of Chinese Spring (RefSeqv1.0). By sowing recently released cultivars and near-isogenic lines in the field at both conventional and deep sowing depths, we confirmed that Locl-A1 was associated with increased emergence from depth in the presence and absence of conventional dwarfing genes. Flanking markers IWB58229 and IWA710 were developed to assist breeders to select for long coleoptile wheats. Increased coleoptile length is sought in many global wheat production areas to improve crop emergence. The identification of the gene Lcol-A1, together with tools to allow wheat breeders to track the gene, will enable improvements to be made for this important trait.